Executive Function and Psychosocial Adjustment in Adolescent Survivors of Pediatric Brain Tumor. Issue 2 (17th February 2021) - Puhr, A.; Ruud, E.; Anderson, V.; Due-Tønnessen, B.J.; Skarbø, A.B.; Finset, A.; Andersson, S.
ABSTRACT: Adolescent survivors of pediatric brain tumor (PBT) are a sparsely studied subset of childhood cancer survivors. Sustaining a PBT may complicate the development of executive functions (EFs), which play a vital role in long-term psychosocial adjustment. In this study, 48 adolescent survivors and their parents completed questionnaires assessing EF, psychological symptoms, fatigue, and adaptive functioning, and 26 survivors underwent neuropsychological assessment. Survivors reported significantly more problems with adaptive functioning than a healthy control group, and this was most strongly associated to executive dysfunction, compared to psychological symptoms and fatigue. The findings have important implications for long-term follow-ups.